1992
DOI: 10.1111/j.1464-410x.1992.tb15450.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Clinical Methods of Measurement of Urinary Frequency and Functional Bladder Capacity

Abstract: We assessed the agreement between 2 methods of data gathering of particular interest in urology: patient questionnaire and examination vs. frequency-volume charts. One hundred consecutive patients consulting our out-patient clinic were chosen for this study; 88 completed the study. Urinary frequency and bladder capacity were evaluated in each patient by using the above methods. The agreement between different methods of measurement was assessed by determining whether the 2 methods were interchangeable, a condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 4 publications
4
20
0
2
Order By: Relevance
“…The higher mean voided volume and the lower frequency found by Larsson and Ramstr˛m also ¢t this hypothesis. The disparity in inclusion and de¢nitions may account for the apparently di¡erent distribution of the sensation related voidings between the two studies.The results in Table III provide clear evidence to what has been numerously speculated before, that in everyday life the bladder is not used to its full extent and voiding most frequently occurs without desire [McCormack et al, 1992;Palnaes Hansen and Klarskov, 1998;Fink et al, 1999]. These results also show that an urgent desire to void (grade 4) cannot be considered as a normal sensation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The higher mean voided volume and the lower frequency found by Larsson and Ramstr˛m also ¢t this hypothesis. The disparity in inclusion and de¢nitions may account for the apparently di¡erent distribution of the sensation related voidings between the two studies.The results in Table III provide clear evidence to what has been numerously speculated before, that in everyday life the bladder is not used to its full extent and voiding most frequently occurs without desire [McCormack et al, 1992;Palnaes Hansen and Klarskov, 1998;Fink et al, 1999]. These results also show that an urgent desire to void (grade 4) cannot be considered as a normal sensation.…”
Section: Discussionsupporting
confidence: 76%
“…However, the accuracy of the volume measurement during cystometry has been questioned because of the unphysiological method of testing. It has been shown that cystometric bladder capacity can be up to twice the value recorded on frequencyvolume charts [Diokno et al, 1987;McCormack et al, 1992]. None of these studies correlated the grade of perception of bladder fullness to the volumes recorded on frequency-volume charts.…”
Section: Discussionmentioning
confidence: 97%
“…In 95 older people (age 72±5.3 years), Asplund and Åberg [10]found a mean voided volume at night of 256±113 ml (versus 222±101 ml in our group) and a mean voided volume in the daytime of 188±86 ml (versus 188±77 ml in our group). McCormack et al [3]assessed the agreement between patient questionnaire and frequency–volume charts in 88 patients. They found a mean diurnal voided volume of 176±64 ml and a mean voided volume at night of 233±130 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen and Klarskov [2]reported that recordings on frequency–volume charts are valid. McCormack et al [3]assessed the agreement between patient questionnaire and frequency–volume charts. They reported a poor agreement between patient questionnaire– and chart–determined urinary frequency, suggesting that a frequency–volume chart shows a more valid indication of urinary habits, than the patient questionnaire itself.…”
Section: Introductionmentioning
confidence: 99%
“…In questionnaires the levels of fluid consumption were consistently underestimated. The same is true for subjectively estimated urinary frequency compared with chart-determined urinary frequency (McCormack et al, 1992). Considering these methodic biases, the low number of studies, and the small patient groups, the results of the available clinical studies do not prove a significant effect of hydration status on the susceptibility to UTI.…”
Section: Prophylactic Approachesmentioning
confidence: 99%